Peasant cooperative "Kopaonik", in Rvati, a Case Study of Collectivization in the Yugoslav Countryside after the Second World War - Virijević, Vladan A. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
Collectivization, as a method of the socialist transformation of village and of organizing agricultural production, was conducted after 1944, lasted until 1953, and it was intensified especially after 1948, namely after the conflict of the Yugoslav country and the party management with members of the Inform Bureau – the Soviet Union and the countries of „national democracy“, when it was abandoned despite the attempt of reorganization. Economic failures of collective farms, political damage caused by relations with farmers, as the most numerous social category, then new possibilities for help and loans from the west, predetermined this step. Aspirations of the Communist party of Yugoslavia to skip the natural way of development and substitute it by an administrative centralization of the production means turned out to be a complete failure. Collective farm „Kopaonik“ located in Rvati near Raška was one of numerous farms of that kind due to which there were intentions to introduce socialism into the village and to transform properties. Despite the efforts of the parties‘ forums and initial positive results, it was soon obvious that conducting this ideological concept was at variance with traditional relations of the patriarchal farmers‘ society. Unprofitability and destimulation of agricultural production, personal vanities and misunderstandings among members, as well as a series of other limiting factors, resulted in its reduction in 1954.